POSTERIOR POLAR ANNULAR CHOROIDAL DYSTROPHY: A CASE SERIES. (2017) - Lenis, Tamara L.; Klufas, Michael A.; Randhawa, Sandeep; Sharma, Mithlesh; Sarraf, David
Abstract : Purpose: To describe the multimodal imaging findings of posterior polar annular choroidal dystrophy (PPACD). Methods: Retrospective case series of 2 patients diagnosed with PPACD. Spectral-domain optical coherence tomography, fundus autofluorescence, and fluorescein angiography findings of PPACD are described. Electroretinography results are also presented. Results: Both patients presented with bilateral peripapillary atrophy extending to involve the temporal arcades in an annular, foveal sparing pattern. Both cases demonstrated outer retinal atrophy with foveal sparing on spectral-domain optical coherence tomography, and fluorescein angiography illustrated corresponding window defects with late staining. Fundus autofluorescence showed hypoautofluorescence in the center of atrophic areas but hyperautofluorescence at the leading edge. Electroretinography findings included cone loss with rod preservation. Inflammatory and infectious workup was unremarkable in both cases. Conclusion: This report describes the multimodal imaging findings of a rare and poorly described chorioretinal disorder, PPACD, and will serve to guide clinicians regarding the evaluation and management of this elusive condition. Abstract : This case series describes two patients with posterior polar annular choroidal dystrophy. Multimodal imaging reveals features of disease that highlight both pathophysiology and clinical spectrum.